A Better Zn-Ion Storage Device: Recent Progress for Zn-Ion Hybrid Supercapacitors - Jin, Jialun; Geng, Xiangshun; Chen, Qiang; Ren, Tian‑Ling (Nano-Micro Letters, 2022)
As a new generation of Zn-ion storage systems, Zn-ion hybrid supercapacitors (ZHSCs) garner tremendous interests recently from researchers due to the perfect integration of batteries and supercapacitors. ZHSCs have excellent integration of high energy density and power density, which seamlessly bridges the gap between batteries and supercapacitors, becoming one of the most viable future options for large-scale equipment and portable electronic devices. However, the currently reported two configurations of ZHSCs and corresponding energy storage mechanisms still lack systematic analyses. Herein, this review will be prudently organized from the perspectives of design strategies, electrode configurations, energy storage mechanisms, recent advances in electrode materials, electrolyte behaviors and further applications (micro or flexible devices) of ZHSCs. The synthesis processes and electrochemical properties of well-designed Zn anodes, capacitor-type electrodes and novel Zn-ion battery-type cathodes are comprehensively discussed. Finally, a brief summary and outlook for the further development of ZHSCs are presented as well. This review will provide timely access for researchers to the recent works regarding ZHSCs. Highlights: 1 The advances of electrode materials, energy storage mechanisms, electrolytes and applications for Zn-ion hybrid supercapacitors (ZHSCs) are comprehensively summarized. 2 Recent progresses in ZHSCs are discussed by categorizing into two configurations of Zn//Cap and Cap//ZBC. 3 Future opportunities and challenges for the development of ZHSCs are also elaborated.